Leonard Bernstein and the Language of Jazz - Baber, Katherine A., 1981- (Book collections on Project MUSE., 2019)
For Leonard Bernstein, music was a language capable of communicating more directly than in words, and jazz was a crucial part of his musical vocabulary. As an idiom made up of a range of styles - whether stride, boogie-woogie, swing, bebop, or cool - jazz was central to Bernstein's compositional aesthetic, particularly in his approach to tonality and to defining American music. The blues, as a special part of this jazz idiom, also helped Bernstein articulate a personal identity, expressing everything from sensuality to humor to loss and isolation. This text will examine the shifting meanings of Bernstein's jazz language in theatrical and symphonic works from across his career.